Analisis Metode Multi Objective Optimization On The Basis Ratio Analysis pada Pengadaan Bahan Baku Kosmetika PT. Zoey Cosmedica Putra - Mohammad Palah, Johan; Agustina, Fenni (Rifa'Institute, 2022)
Supervision, procurement and maintenance of good raw materials are really needed to increase production potential and production costs. PT. Zoey Cosmedica Putra is a cosmetic tolling company, which is a business collaboration between individuals/companies and cosmetic manufacturers who have permits in the manufacture of cosmetic products. PT. Zoey Cosmedica Putra procures raw materials only based on last month's stock availability without taking other factors into account. Therefore, it is necessary to take into account those who are able to provide alternative value to PT. Zoey Cosmedica Putra in determining the maximum procurement of raw materials in order to obtain minimal profits, risks and expenses. The use of the Multi Objective Optimization Method based on Ratio Analysis (MOORA) is a solution related to the needs of PT. Zoey Cosmedica Putra in determining the procurement of raw materials by providing a priority rating of each raw material with criteria, determination of criteria and weights that adjust to the company's needs, namely expiration, inventory, raw material prices, intensity of use, and delivery from producers where each criterion has its own set. -each -each. This calculation is to support decisions in procuring raw materials. with an accuracy rate of 76 percent.